Design and Fabrication of Metformin-Loaded Tri-Layer PCL/PVA/PCL Scaffolds for Chronic Wound Healing - CESUR, SÜMEYYE; GÜNDÜZ, OĞUZHAN (My University, 2022)
Chronic wounds occur when an acute wound cannot complete the normal wound healing process that takes 4-8 weeks. The recurrence rate of chronic wounds is 70% and is more common in people with diseases such as diabetes and obesity [1]. Therefore, healing chronic wounds is a very challenging and costly process. Chronic wounds have higher inflammation and reducing inflammation is a promising approach for healing these wounds [2]. Metformin is an antidiabetic drug used for the treatment of diabetes. However, the anti-inflammatory effect of metformin has recently attracted attention for its use in wound healing [3]. 3D-printed scaffolds mimic the extracellular matrix (ECM) to support cell attachment and proliferation at the wound healing site and these scaffolds could be loaded with drugs, growth factors, and other agents for increasing wound healing [4]. In this study, tri-layered PCL/PVA/PCL and PCL/PVA-Met/PCL scaffolds were produced by using an extrusion 3D printer for chronic wound healing. The characterization of the scaffolds was done with Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), and the tensile test machine. The average pore size of the PCL/PVA/PCL and PCL/PVA-Met/PCL scaffolds was 82,96±4,018 and 63,60±4,039 μm, respectively. Both scaffold's pore sizes were within a limit that allows skin regeneration. The FTIR and XRD results were in compromise with each other, demonstrating that Metformin was successfully encapsulated in the polymer solution. In vitro drug release of Metformin was analyzed with a UV spectrophotometer. The upper and lower PCL layer in the tri-layered structure provided sustained release of the drug. Less than 50% of the drug was released in 24 hours, but it reached 100% on day 31. The biocompatibility of the scaffolds was also investigated with the MTT test. The test showed that both scaffolds were non-toxic and these Metforminloaded tri-layered scaffolds could have a promising potential for the treatment of chronic wounds.
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Chronic Wounds; Wound Healing; 3D Printing; Scaffolds; Metformin